"A call for a clear assignment" – A focus group study of the ambulance service in Sweden, as experienced by present and former employees. (January 2018) - Rosén, Helena; Persson, Johan; Rantala, Andreas; Behm, Lina
Highlights: The AS was described as complex, including different patients and settings. The participants perceived the ambulance mission statement as unclear. There is a discrepancy between the anticipated assignments and the working reality. Abstract: Aim: The aim was to explore the ambulance service as experienced by present and former employees. Background: Over the last decade, the number of ambulance assignments has increased annually by about 10%, and as many as 50% of all ambulance assignments are considered non-urgent. This raises questions about which assignments the Ambulance Service (AS) is supposed to deal with. Design/method: Data were collected from three focus group interviews with a total of 18 present and former employees of the Swedish AS. An inductive qualitative analysis method developed by Krueger was chosen. Results: Five themes emerged in the analysis: "Poor guidance for practice", "An unclear assignment", "Being a gate keeper", "From saving lives to self-care" and "Working in no man's land", which together constitute the AS. Conclusion: Present and former employees of the AS in Sweden describe their mission as unclear and recognize the lack of consensus and a clearly developed mission statement. Furthermore, expectations and training mainly focus on emergency response, which is contrary to the reality of the ambulance clinicians' everyday work.